AL QUR'AN HADITH LEARNING METHODS FORM A CULTURE OF INDEPENDENCE AND HAPPINESS IN LEARNING: (Studi Kasus di MAN 1 Kota Tangerang) - Wij Lestari; Kerwanto; Imat Ruhimat; Reffy Ananda Rizki (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2024)
This research aims to explain the implementation of the mind map and market day methods to achieve completeness in learning Al-Qur’an-Hadis in a fun manner at MAN 1 Tangerang. The scope includes cooperative learning media and learning methods. The method used is descriptive qualitative. Data collection through interviews with data triangulation. The results of this research show that the mind map and market day methods make students learn creatively and happily. The impact on learning outcomes is cognitive completeness and completeness in psychomotor competence. The benefit of this article can be as a reference for educational practitioners in using various methods. The implication of this research is that the thr process of learning Al-Qur’an-Hadis becomes enjoyable and the learning outcomes are complete cognitive (psychomotor). Suggestions for further research include quantitative research to see the magnitude of the influence of each variable.